Santiago Zapata Blanco, Amélia Branco, Inocêncio Seita Coelho, Francisco Manuel Parejo Moruno, Isabel Saraiva y José Neiva Vieira (coords.). Jaime Salazar Sampaio. Textos de Economia corticeira 1951-1988. Bragança, Instituto Politécnico de Bragaça, 2014. - Rangel Preciado, José Francisco (Investigaciones de Historia Económica, 2019)
Sin resumen